PENGARUH SENTRA BERMAIN PERAN TERHADAP PERCAYA DIRI ANAK DI TK NEGERI PEMBINA 1 PEKANBARU: Dwi listari, Susi Herlinda, Nopa Wilyanita - listari, Dwi; Herlinda, Susi; Wilyanita, Nopa (P3M STKIP 'Aisyiyah Riau, 2024)
The purpose of this study was to determine the level of influence of the role playing center on the confidence of children aged 5-6 years in TK Negeri Pembina 1 Pekanbaru. This research uses a quantitative approach and the type of research is experimental. The sample of this study were all children in TK Negeri Pembina 1 Pekanbaru, as many as 30 children aged 5-6 years. The results of data analysis and research discussion are as follows: Children's confidence in TK Negeri Pembina 1 Pekanbaru after being given the role playing center treatment has increased and is classified as high, meaning that there is an influence of the role playing center on the child's confidence, compared to before the center played the role. The role playing center has a positive influence of 50.13% on the confidence of children aged 5-6 years in TK Negeri Pembina 1 Pekanbaru. The results of this study are far from perfection. For that we need advice and input from various parties. The school needs to add and complete facilities in the school to help teachers implement strategies in learning so that all aspects of child development can develop properly. Teachers should be more creative in determining learning strategies that relate to all aspects of child development, especially related to children's confidence. For further researchers searching and finding alternative learning methods / strategies that can increase early childhood confidence.